2020
DOI: 10.3390/urbansci4020024
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Level Climate Governance in Bangladesh via Climate Change Mainstreaming: Lessons for Local Climate Action in Dhaka City

Abstract: Over the last three decades, Bangladesh has implemented various initiatives to address different climate change impacts. In a multi-level governance arrangement, addressing climate change impacts is often constrained by climate change mainstreaming. In Bangladesh, a crucial question that arises is how mitigation and adaptation efforts are addressed at both national and sub-national levels. This paper examines the integration of climate change issues into national, sectoral, and city development plans with a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…This procedure is conceptualized in Figure 1. As the central planning organization, the Bangladesh Planning Commission is responsible for designing and preparing the short-to long-term national development planning (Fatemi et al, 2020b). Through the Five-Year Plans (FYPs), it determines the overall planning direction for growth and development of the urbanized areas in the country (Damianova et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…This procedure is conceptualized in Figure 1. As the central planning organization, the Bangladesh Planning Commission is responsible for designing and preparing the short-to long-term national development planning (Fatemi et al, 2020b). Through the Five-Year Plans (FYPs), it determines the overall planning direction for growth and development of the urbanized areas in the country (Damianova et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Similar to Fatemi et al ( 2020 ) and Pieterse et al ( 2020 ), the scores were the basis for quantitative comparison and the text data associated with each score formed the basis of qualitative content analysis. The content analysis provided context and evidence of CSA or otherwise in the plans as well as a validation of the quantitative assessment.…”
Section: A Climate-smart Agriculture Mainstreaming Assessment Frameworkmentioning
confidence: 98%
“…To understand CSA mainstreaming in the 2018–2021 MTDPs from the Upper West Region, the study tailored the suggested report structure by the NDPC guidelines for preparing MTDPs in Ghana to general mainstreaming assessment frameworks (Fatemi et al 2020 , p. 4; Pieterse et al 2020 , p. 4). In the NDPC guidelines, there are seven recommended chapters namely: (1) Profile/Current Situation/baseline; (2) Prioritization/key Development Issues; (3) Development Goal, Adopted Objectives and Strategies; (4) Development Programs and subprograms; (5) Annual Action Plan; (6) Monitoring and Evaluation Plan; and (7) Communication Plan.…”
Section: A Climate-smart Agriculture Mainstreaming Assessment Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Floods impacts are projected to be significant, with the World Resources Institute's data indicating a doubling of global flood victims by 2030, from 65 to 132 million and from 7 to 15 million for riverine and coastal flooding, respectively (Kuzma and Luo, 2020). In the phase of climate change impacts, the situation is acute in developing countries, where slow progress in human development, deficits in infrastructure (Fatemi et al, 2020b, unplanned urbanization coupled with rapid loss of natural drainage channels and flood retention areas due to encroachment (Khan et al, 2018) are expected to deepen flood vulnerabilities. Already in the Asia-Pacific region, inundation has intensified and become commonplace in many cities ( UN-Habitat, 2015;Adikari et al, 2010).…”
Section: Introductionmentioning
confidence: 99%